A homogeneidade discursiva em notícias de popularização da ciência nas revistas Ciência Hoje online e Galileu - Lovato, Cristina dos Santos (2014)
This thesis was developed as part of the CNPq projects No. 301962/2007-3 Análise crítica de gêneros com foco em artigos de popularização da ciência (MOTTA-ROTH, 2007), and CNPq No. 301793/2010-7 Análise crítica de gêneros discursivos em práticas sociais de popularização da ciência (MOTTA-ROTH, 2010), concerning the critical analysis of science popularization genre. From an interdisciplinary perspective of analysis, we take as reference the theoretical principles of Systemic Functional Linguistics (HALLIDAY 1994, HALLIDAY, MATTHIESSEN, 2004), Critical Discourse Analysis (FAIRCLOUGH, 1995, 2001, for example) and Sociorethoric (BAZERMAN, 2005; SWALES, 1990, for example), in order to perform an analysis of the science popularization news genre published by the magazines Ciência Hoje Online and Galileu. Our aim is to identify which concept of science is built discursively in 30 science popularization news and identify which sense effect this concept generates for the process of science popularization, investigating their conditions of production, distribution and consumption, by investigating their conditions of production, distribution and consumption. The theoretical and methodological approach used is guided by the three dimensions of analysis suggested by Fairclough (2001): description, interpretation and explanation. In the textual description, we describe and interpret the rhetorical organization of the science popularization genre. We also verify possible register variations. Based on the linguistic categories which are part of the the Engagement Subsystem, we observed how quotes and reports are used to position social actors whose voices are inserted in the news in the form of manifest intertextuality. The results indicate that there are no variations in terms of rhetorical organization in the news analyzed. These texts follow the model of the inverted pyramid, and seem to be short copies of releases and speeches from the scientists who had performed the researchers reported in the news.Another aspect observed concerns a trend towards a conclusive and cumulative view of the results. Regarding genre register variations, we observed that Ciência Hoje Online tends to follow the world of science, through the appropriation of typical discursive patterns of science, and Galileu tends to follow the world of life, through the appropriation of typical discursive patterns of everyday language. We also noticed that the process of dialogic expansion is predominant, but the lack of varied perspectives on popularized scientific discoveries restricts the science popularization discourse to the scientific sphere, in the sense of a discursive homogeneity. The exclusivity of a social actor mentioned by means of manifest intertextuality thus refers to a concept of science built on these texts as a product, result of the effort of an individual, not considering the network of conversations of scientists and hypotheses and controversies that constitutes the nature of scientific activity.